Induction of Unscheduled DNA Synthesis in V79 Cells by Diesel Emission Particles Dispersed in Simulated Pulmonary Surfactant - Z. W. Gu; B. Z. Zhong; M. J. Keane; W. Z. Whong; W. E. Wallace; T. Ong (The National Institute for Occupational Safety and Health (NIOSH), 1995)
"Abstract-Diesel emission particles (DEP) from an engine operating on the Federal Test Procedure VDC were dispersed in an aqueous mixture of dipalmitoyl lecithin (DPL). a major component of pulmonary surfactant and saline and were tested for genotoxicity using the unscheduled DNA synthesis (UDS) assay with autoradiography techniques in cultured Chinese hamster lung cells. A DEP sample from the same source was dispersed in dimethyl sulphoxide (DMSO) and subjected to the same assay. Both dispersions (in DPL and DMSO) were found to induce UDS in a dose-related manner. After separation of the sample into supernatant and sediment fractions. the activity of the DEP sample was found to reside in the supernatant fraction for the DMSO-dispersed sample; and in the sedimentary fraction for the surfactant-dispersed sample. These findings further indicate that genotoxic activity associated with DEP inhaled into the lung may become bioavailable through the dispersion properties of pulmonary surfactant components.INTRODUCTIONTHE mutagenicity of diesel emission particles (DEP) has been studied intensively (LEWTAS and WILLIAMS, 1986). Carcinogenic effects of diesel exhaust in exposed animals have been reviewed (NIOSH, 1988) and an evaluation of carcinogenic risks to humans from diesel engine exhausts has been published (IARC, 1989). Using components of pulmonary surfactant such as dipalmitoyl lecithin (D PL), dipalmitoyl phosphatidylethanolamine (DPPE) or dipalmitoyl phosphatidic acid (DPPA) dispersed in physiological saline, we have previously shown that diesel soots express mutagenic activities in the Salmonella histidine reversion assay system and in the sister chromatid exchange assay using the cultured Chinese hamster lung (V79) cells. Mutagenic activity of diesel soots dispersed in DPL, DPPE and DPPA was quantitatively comparable to and in some cases greater than, the activity expressed by an equal mass of soot extracted by dichloromethane-dimethyl sulphoxide (DCM-DMSO) (WALLACE et al., 1989).Unscheduled DNA synthesis (UDS) is accepted and frequently included, as one of the tests in the battery of assays used to assess carcinogenic-mutagenic potential -of chemicals (MITCHELL et al., 1983). In this study, induction of UDS in V79 cells by DEP, dispersed in the major component of pulmonary surfactant DPL, was carried out. The purpose of this study is to validate the suggestion generated from our previous work that mutagens associated with inhaled particles may be dispersed or solubilized in the phospholipid component of pulmonary surfactant and become active in such a phase (WALLACE er al., 1989) and to test the fractionated DEP sample using UDS assay for a more complete evaluation of its genotoxicity."